Reclaiming Indigenous Sign Languages and Supporting Accessibility and Inclusion for Indigenous Deaf Children and their Families - Snoddon, Kristin; Ireland, Dominique; Abram, Joel; Ireland, Marsha; Ireland, Max; Osawamick, Elizabeth; Tanner, Shelly; Osawamick-Sagessige, Miigwaans; Tanner, Shayla-Rae (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2024)
This paper reports data from a research study and workshop about reclaiming Indigenous sign languages and cultures, and strengthening services for Indigenous deaf children and their families and communities. The purpose of this workshop was for presenters to share their lived experiences and knowledge as deaf and hearing Elders, parents, and youth, including what resources were and were not available to them. Findings revealed themes including the importance of support for accessibility and inclusion from First Nations political and community leadership; the importance of supporting children’s intersectional identities; the need for greater resources for First Nations communities to access services and supports for deaf children; and youth experiences of learning about deaf culture and sign language, and attending deaf schools. These findings also suggested innovative models for including deaf children and their families.